Faith and leadership: understanding the influence of faith on the leadership experiences of women leaders in higher education - Patel, Dimple, author; Anderson, Sharon K., advisor; Kuk, Linda, committee member; Lange, Alex, committee member; Tungate, Susan, committee member (Colorado State University. Libraries, 2025)
The purpose of this study was to understand how faith influenced women leaders in higher education. The specific research question was: "How do women who are senior leaders in higher education describe the influence of faith on their leadership experiences?" This was a qualitative research study utilizing a phenomenological approach for data analysis and interpretation. The data were collected from nine women leaders in senior leadership roles in higher education. Each of the women leaders in this study are deeply connected to their faith. Though they defined faith in their own terms, they all agreed to the definition of faith for this study: a belief and trust in a transcendent being. In the current study, the term transcendent being can be called God, Allah, Vishnu, Shiva, or another name and does not require a religious affiliation. This study produced four important findings. First, the influence of faith on the participants' leadership experiences begins with each one of them exercising faith-driven leadership. They exercised faith-driven leadership through their co-creating relationship with a transcendent being, which they all referred to as God. The influence of faith also served as a foundation for their overall leadership ethos, comprising values and lessons, both a part of faith-driven leadership. The values or guiding principles they associated with their leadership were derived from their faith. Sometimes they also utilized lessons learned from their faith in how they led or what they did in their leadership roles. Second, the influence of faith on their leadership encouraged them to promote inclusion and equity. They practiced open-mindedness and fairness. Third, how and why the women leaders persevered was attributed to the influence of their faith. They demonstrated resilience in a variety of situations, including moments when the influence of faith was visible to others—an experience that sometimes left them feeling exposed, misunderstood or vulnerable. Finally, the influence of faith brought these nine women blessings and opportunities for connection.
Keywords: higher education; leadership; women leaders; influence of faith; faith; women